Alveolar nitric oxide concentration reflects peripheral airway obstruction in stable asthma. Issue 3 (21st March 2013) - Fujisawa, Tomoyuki; Yasui, Hideki; Akamatsu, Taisuke; Hashimoto, Dai; Enomoto, Noriyuki; Inui, Naoki; Nakamura, Yutaro; Maekawa, Masato; Suda, Takafumi; Chida, Kingo
<x xml:space="preserve">Abstract</x> In stable asthmatics, alveolar nitric oxide concentration (CANO) correlated with FEF25–75, FEF50, FEF25–75 %pred and FEF50 %pred, spirometric parameters of small airway obstruction. It also correlated with age and asthma duration. CANO seems to be a more specific marker of peripheral airway obstruction than FeNO and central airway NO flux.